Analisis kemampuan berpikir kritis matematis siswa kelas VII di SMPN 5 tapung hulu pada materi aritmatika sosial - Endang Safitri; Astri Wahyuni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
The main objective of this study was to assess and explain the mathematical critical thinking skills demonstrated by students when engaging with Social Arithmetic problems. This study used a descriptive qualitative research approach and was conducted at SMPN 5 Tapung Hulu. The participants were selected based on characteristics and information relevant to the research questions, consisting of 28 seventh grade students. The data collection instrument consisted of a three-item essay assessment designed to measure mathematical critical thinking skills. The data analysis process involved four main stages: data collection, data reduction, data presentation, and conclusion drawing. The results of this study are the overall mathematical critical thinking skills of students on Social Arithmetic material at SMP Negeri 5 Tapung Hulu classified in the moderate category, with an overall average value of 68.48. The indicator with the highest score is the ability to state what is asked in the question correctly, with an average score of 70.75. Meanwhile, the indicator with the lowest score is the ability to make appropriate conclusions, with an average score of 70.75.